Ramos Rodríguez, Froilán. Guerra Fría Global. el Pensamiento Militar Chileno y Venezolano (1960-1970). Santiago de Chile, Centro de Estudios Bicentenario, 2022 - Garay-Vera, C (University of Sevilla, 2024)
[No abstract available]